THE VACCINATION AGAINST VARICELLA. THE ANSWERS TO THE PEDIATRISTS QUESTIONS - V.К. Tatochenko ("Paediatrician" Publishers LLC, 2009)
Varicella is a disease which can be stopped by methods of specific prophylaxis. At the same time, there are no official recommendations on vaccinal prophylaxis of varicella in Russia nowadays. The article presents the answers to the most frequently asked questions of pediatrists concerning vaccination techniques, its effectiveness and safety, and vaccination in epidemic nidus. Special attention was given to the questions of vaccinal prophylaxis of varicella in immunocompromised patients. Key words: varicella, prophylaxis, vaccination. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(3):114-119)